Construction of Self-Identity of teenagers Using Instagram Social Media : Phenomenological Study at Islamic University of North Sumatera (UINSU) - Putri Anjeli, Shakira; Jamil, Khoirul (The International Journal of Politics and Sociology Research, 2024)
The research explores how Instagram plays a role in strengthening the religious identity of teenagers, specifically focusing on UINSU students from the Class of 2020. Utilizing a qualitative phenomenological approach, the study involved 7 informants from the Department of Communication Science and Islamic Counseling Guidance. The findings reveal that Instagram is a crucial platform for teenagers to reflect upon and reinforce their religious identity, particularly through sharing religious content such as preaching clips. An inclusive campus environment positively impacts this identity formation, encouraging students to express and solidify their religious beliefs. The motivations behind sharing religious content include providing knowledge, offering motivation, and conveying da’wah. However, the use of Instagram can also lead to identity conflicts between religious values and the desire for personal expression. This study provides a new perspective on how social media influences the formation of teenagers' religious identity and highlights the complexity of maintaining this identity in both the digital world and everyday life